EXPLANATORY STUDY: THE IMPACT OF TRUST IN KASKUS ON KASKUSERS PURCHASE INTENTION - Lukmanjaya, Aditya (University of Surabaya, 2013)
Big potential market in Virtual Communities (VCs) make Consumer toConsumer (C2C) websites focusing on increasing their customer bases byconverting members of their VCs into C2C buyers and sellers. This phenomenonis called e-commerce based on social network (ESN). One of Indonesiaâs wesbitewhich apply ESN is Kaskus. The objective of this study is to propose a frameworkon the understanding of how trust in Kaskuser and trust in www.kaskus.co.id orvendors in Kaskus affect purchase intention.A questionnaire was adopted from Lu et al. (2010) for online survey. Nonprobability sampling method is used for collecting data. The sample consisted of210 registered member of Kaskus. Data were analayzed through descriptivestatistics, SPSS, and LISREL.Result of the study finds the positve impact of trust in Kaskus on Kaskuserâspurchase intention. All antecedents of trust are proved have postive impact onboth trust in members and trust in website/vendorâs which lead to intention to getinformation, and purchase intention thereafter. However, trust in Kaskuser showsnegative impact on www.kaskus.co.id or trust in vendors. In addition, from allantecedents of trust, structural assurances has the greatest impact into Kaskuserâspurchase intention.